PERAWATAN AMELOBLASTOMA DENGAN METODE DREDGING (LAPORAN KASUS) - Herry Gunadi; Arfiandri Roesli (Faculty of Dentistry, Universitas Indonesia, 2015)
A case report of successful Ameloblastoma treatment by Dredging Method, in left mandibular resgion of 25 years old female. Dredging was taken three times with six months period, following enucleation three months before. Evaluation of the effectiveness of this procedure showed from histopathological examination, panoramic radiograph and the mandible attained normal form and function.